A ZnO@ABS/TPU/CaSiO3 3D skeleton and its adsorption/photocatalysis properties for dye contaminant removal. Issue 68 (11th November 2020) - Zhang, Mengli; Xia, Xinshu; Cao, Changlin; Xue, Hun; Yang, Yujin; Li, Wei; Chen, Qinghua; Xiao, Liren; Qian, Qingrong
Abstract : Enhanced synergistic effect of photocatalytic and adsorption was realized through the system constructed of ZnO nanoparticle loaded 3D skeleton. Abstract : Both adsorption and photocatalysis are considered to be effective methods for removing organic contaminants from dye wastewater. In this study, the construction of 3D skeletons based on the nanoparticles ZnO and ABS/TPU/calcium silicate (CaSiO3 ) (shortened as ATC) were fabricated via fused deposition molding (FDM) technology. Characterization by scanning electron microscopy (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) depicted that ZnO nanospheres had been successfully grown on the 3D skeleton surface with an enlarged specific surface area. As the results of the RhB adsorption and photocatalytic degradation experiments showed, the removal ratio of RhB onto the ZnO-ATC skeleton was as high as 97.94% and the synergistic effect of adsorption and photocatalysis greatly shortened the RhB degradation time under ultraviolet light irradiation. The nanocomposites synthesized in this study showed a significant removal ability for organic pollutants, and could effectively overcome the limitation of the secondary removal of photocatalysts.